Pengaruh Motivasi Berprestasi dan Stres terhadap Prestasi Akademik Mahasiswa Tahap Akademik Kelas Internasional Program Studi Pendidikan dan Profesi Dokter Fakultas Kedokteran Universitas Indonesia - Yogie Afdhal (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2020)
The purpose of this study was to know correlation between achievement motivation and stress on the academic achievement of international class student Faculty Medicine Universitas Indonesia. Total 64 of 176 students were used as research samples to obtain data then analyzed using the quantitative method of path analysis. The result of this study indicate that (1) there is a positive correlation between achievement motivation and academic achievement, (2) there is a negative correlation between stress and academic achievement, (3) there is a negative correlation between achievement motivation and stress.